The Effect of Internet Adoption on the Profitability of Commercial Banks in Kenya - Gatitu, Simon Njega (University of Embu, 2020)
Information technology has opened up new ways in which banks can carry out their operations in satisfying their consumer needs. The growing uptake of internet banking in the banking sector has helped in access to financial services tremendously. The study sought to determine the effect that the internet has on the profitability of commercial banks. It was guided by the following questions; what is the effect of cost on internet-based banking? What is the effect of technology issues on the adoption of internet banking? What is the effect of internet security on the internet-based transaction? What is the effect of profitability on the adoption of internet banking? The study used secondary obtained for various Central Bank of Kenya publications and journals. The study covered a period of 5 years from 2014 to 2018. The findings show that there is a significant positive relationship between profitability and internet banking. This is because internet banking cuts banks costs, increase commission income, reduce staffing levels, and make banking more convenient for customers. However, the banks are faced with cyber-attacks which have created doubt about the adoption of internet banking among customers and banks. The study recommends that banks should adopt internet banking as it fast, effective, and easy to use in delivery in their services. Banks should ensure internet banking security to boost consumer confidence. This is to create trust and security to avoid undesirable consequences in the face of a risky decision.